CONDUCTING BIOLOGICAL SCIENCE PRACTICUM AT A DISTANCE AT UNIVERSITAS TERBUKA, INDONESIA - Yuni Tri Hewindati; Aminudin Zuhairi (AAOU Journal, 2009)
Conducting biological science practicum at UT involves a series of activities, ranging from registration, implementation, practicum learning support, and evaluation of student learning. Some important factors to consider in conducting science practicum at a distance include location, student conditions, and availability of the needed resources. UT science practicum involves the use of resources of partner universities, so the practicum is conducted during the semester break of the partner institution. In order to be financially viable, practicum is conducted when there are a minimum of 8 participating students, otherwise students will have to meet the minimum quota of the practicum cost.